2016
DOI: 10.1248/bpb.b16-00046
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ginsenoside Rg1 on Bleomycin-Induced Pulmonary Fibrosis in Rats: Involvement of Caveolin-1 and TGF-β1 Signal Pathway

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive disease with poor prognosis and high mortality rate. Panax Notoginseng Saponins (PNS), extracted from Panax Notoginseng as a traditional Asian medicine, displayed a significant anti-fibrosis effect in liver and lung. However, whether Ginsenoside Rg1 (Rg1), an important and active ingredient of PNS, exerts anti-fibrotic activity on IPF still remain unclear. In this study, we investigated the effect of Rg1 on bleomycin-induced pulmonary fibrosis in rats. Bleom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In terms of normal cells, Zhan et al reported that ginsenoside Rg1 exerted protective effect on bleomycin-induced pulmonary fibrosis in rats by increasing the expression of CAV1 mRNA and protein [168]. Nakaso et al reported that knockdown of Cav-1 and/or Cav-2 prevented the protective effects of tocotrienol in a cellular Parkinson's disease model [169].…”
Section: Cav-1 and Oxidative Stress Regulationmentioning
confidence: 99%
“…In terms of normal cells, Zhan et al reported that ginsenoside Rg1 exerted protective effect on bleomycin-induced pulmonary fibrosis in rats by increasing the expression of CAV1 mRNA and protein [168]. Nakaso et al reported that knockdown of Cav-1 and/or Cav-2 prevented the protective effects of tocotrienol in a cellular Parkinson's disease model [169].…”
Section: Cav-1 and Oxidative Stress Regulationmentioning
confidence: 99%
“…HYP is a common index for collagen quantification (31). A previous study verified that BLM-induced fibrosis was associated with an increased lung coefficient and HYP content (32). CD4 + T (helper) cells have an important role in the immune system, which not only help macrophages respond to intracellular antigens but also help B cells form germinal centers (33).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, SML reduced the expression of both TGF-β1 and SMAD4. Similar to SML, many natural compounds including berberine [ 13 ], daidzein [ 30 ], and ginsenoside Rg1 [ 31 ] exerted protective effect by intervening the TGF-β/SMAD signalling pathway. The advantage of using natural products, including SML, is that they usually do not induce significant side effects in body even with a long-term application.…”
Section: Discussionmentioning
confidence: 99%